Positioning discourse on homophobia in schools: What have lesbian and gay families got to say?. (September 2019) - Cocker, Christine; Hafford-Letchfield, Trish; Ryan, Peter; Barran, Charlotte
This paper reports findings from a study in England, which investigated the experiences of lesbian and gay parents in relation to homophobia in primary and secondary schools. The study was part of a larger European Union project investigating the impact of family and school alliances against homophobic and transphobic bullying in schools across six nation states. Qualitative in-depth semi-structured interviews with seven lesbian and gay parents from five families were conducted to explore their unique experience and perspectives on these issues. Discourse analysis was used to facilitate understanding of how lesbian and gay families negotiated the outsider/insider and public/private spheres of the school and communities of which they were a part. Parents identified a number of strategies to address their experiences of homophobia within schools. The findings have implications for how social work recognises and promotes diversity and equality when working with lesbian, gay, bisexual and transgender families, as social workers have a powerful role in supporting families. This involves recognising the strengths of lesbian, gay, bisexual and transgender families in their assessments.